Glucose Sensing by Time-Resolved Fluorescence of Sol-Gel Immobilized Glucose Oxidase - Maria Lepore; Raffaele Velotta; Carlo Altucci; Sergio De Nicola; Bartolomeo Della Ventura; Rosario Esposito; Damiano Gustavo Mita (Sensors, 2011)
A monolithic silica gel matrix with entrapped glucose oxidase (GOD) was constructed as a bioactive element in an optical biosensor for glucose determination. Intrinsic fluorescence of free and immobilised GOD was investigated in the visible range in presence of different glucose concentrations by time-resolved spectroscopy with time-correlated single-photon counting detector. A three-exponential model was used for analysing the fluorescence transients. Fractional intensities and mean lifetime were shown to be sensitive to the enzymatic reaction and were used for obtaining calibration curve for glucose concentration determination. The sensing system proposed achieved high resolution (up to 0:17 mM) glucose determination with a detection range from 0:4 mM to 5 mM.